(untitled) (Південний архів (історичні науки), 2022)
Purpose. The aim of this paper is to analyze the transformational processes taking place in the cultural space of a modern European global city. Particular attention is paid to highlighting its structural elements through the prism of cultural processes, as well as factors influencing the modernization of the urban cultural environment on the example of the largest Western European cities. Methods. The research methodology is based on the principles of historicism and objectivity. Considering the versatility of the modern European global city, a systematic and integrated approach to its study was used. The study involves both general methods (the method of system-structural analysis, analysis and synthesis) and special methods: culturalsemantic, cultural-historical, socio-cultural and statistical. With the help of the cultural-semantic method, the cultural environment of the city was studied, with the subject-spatial environment being its object. In order to identify changes in the cultural space of cities that have occurred over the past decade, the cultural-historical method was used. Socio-cultural method helped examine the dynamics of the cultural environment of the city in relation to its social dynamics (sociocultural processes occurring in its environment). The statistical method made it possible to record quantitative indicators of the content of cultural space of the largest global cities, which made possible its detailed analysis. Results. The results of the study led to the conclusion that the modern European global city is becoming not only an important center of the world economic and political system, but also a cultural phenomenon that is gaining more and more European and global significance. The emphasis is on the fact that its cultural space should be considered as a certain system in space and time, which creates opportunities for the creative, rich spiritual life of each of its individual inhabitants, and the form in which the life of urban culture takes place. It was revealed that the historical transformation of the European global city ‒ from industrial to post-industrial ‒ created its new topography, as a result, the cultural space expanded, its structure, quantitative and qualitative parameters became much more complicated. The fullness of the cultural space of the largest Western European cities is analyzed. It has been established that the best indicators in this area are demonstrated by London and Paris. Conclusions. Based on the results of the study, it can be concluded that the cultural space of global megacities is constantly transforming and modernizing, successfully combining, on the one hand, historical and cultural sights of the past, and on the other hand, modern elements of innovative and creative culture. It has been established that its transformation is influenced by the processes of globalization, internationalization and gentrification, which are manifested in the emergence of many interesting initiatives, which indicates decentralization, completeness and accessibility of urban cultural space.